Multi-Brand Strategy in Maintaining Consumer Loyalty in Companies During Economic Downturn - Budianto W. E; Haryono C. G, Padmalia M (Publikasi Indonesia, 2026)
The decline in consumer purchasing power in recent years has increased price sensitivity and driven consumers to be more selective in their purchasing decisions, including in essential educational product categories such as notebooks. This situation requires companies to adopt more adaptive marketing strategies, one of which is the multibrand strategy. This study aims to analyze the effect of multibrand strategy on consumer loyalty and examine the moderating role of declining purchasing power in this relationship. A quantitative explanatory research design was employed, involving 75 respondents who used notebook products from APP Sinarmas (SIDU, Dodo, and Skola). Data were analyzed using linear regression and moderation analysis. The results reveal that the multibrand strategy has a positive and significant effect on consumer loyalty. Declining purchasing power does not directly affect loyalty; however, it significantly moderates and strengthens the relationship between multibrand strategy and consumer loyalty. These findings highlight the importance of a diversified brand portfolio as an effective retention mechanism during periods of economic pressure. This study offers practical implications for companies in designing adaptive branding strategies and theoretical contributions to the literature on brand portfolio management under fluctuating economic conditions.